2010
DOI: 10.1371/journal.pone.0013158
|View full text |Cite
|
Sign up to set email alerts
|

Zip4 (Slc39a4) Expression is Activated in Hepatocellular Carcinomas and Functions to Repress Apoptosis, Enhance Cell Cycle and Increase Migration

Abstract: BackgroundThe zinc transporter ZIP4 (Slc39a4) is important for proper mammalian development and is an essential gene in mice. Recent studies suggest that this gene may also play a role in pancreatic cancer.Methods/Principal FindingsHerein, we present evidence that this essential zinc transporter is expressed in hepatocellular carcinomas. Zip4 mRNA and protein were dramatically elevated in hepatocytes in the majority of human hepatocellular carcinomas relative to noncancerous surrounding tissues, as well as in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 52 publications
0
73
0
Order By: Relevance
“…To the best of our knowledge, this is the first report on subcellular distribution of zinc transporters in the liver regardless of alcohol exposure. Although ZIP4 has been detected in human liver at the tissue level (31,32), information on subcellular distribution of zinc transporters in human liver is not available. Therefore, one limitation of the study is that the data of hepatic zinc transporters lack support by human data.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first report on subcellular distribution of zinc transporters in the liver regardless of alcohol exposure. Although ZIP4 has been detected in human liver at the tissue level (31,32), information on subcellular distribution of zinc transporters in human liver is not available. Therefore, one limitation of the study is that the data of hepatic zinc transporters lack support by human data.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of ZIP4 is associated with pathogenesis and progression in cancer and carcinomas (238,244,438). In the case of pancreatic cancer, ZIP4 enhances CREB activity by the uptake of zinc, which transcriptionally increases miR-373 expression, leading to silencing of molecules with tumor suppressor activity (459).…”
Section: Zip4 (Liv-1 Subfamily)mentioning
confidence: 99%
“…With respect to the genes shown in Table 1, SLC39A4 (also named ZIP4) is zinc transporter and it has been shown that ZIP4 expression in Hepatocellular Carcinomas serves to repress apoptosis, enhancing cell cycle and increasing migration [28]. Also, Xu et al have shown in hepatocellular carcinomas that suppression of ZIP4 reduced cell migration and invasiveness, whereas ZIP4 over expression caused increasing of cell migration and invasiveness [29].…”
Section: Fisher's Analysismentioning
confidence: 99%